Perancangan Wacinwa: Sang Manggalayudha - Aneng Kiswantoro (Wayang Nusantara: Journal of Puppetry, 2019)
The purpose of this design work is to make Wacinwa dolls that are tailored to the interests and needs of the designer in the show. The making of puppets is motivated by the constraints in the availability of puppets for staging. Meanwhile, Wacinca is only owned by Yogyakarta’s Sonobudoyo Museum. Besides the Wacinwa doll, the collection of Sonobudoyo Museum is too small, its head is detached from the body, and it is difficult to move. The characters made are figures in working on the Wacinwa story entitled Sang Manggalayuda. The Hawkins (1991) method of designing stages is used in this work. The stages are the first stage of exploration, namely setting themes, ideas, and titles of works and thinking, imagining, feeling, and searching in order to interpret ideas and ideas. The second stage is the experimentation stage, which is trying to choose, differentiate, consider in order to find harmony and find integrity and unity in various experiments. The last stage is the formation stage, which is to determine the form of design by combining the symbols of the results of the trials conducted. After the figures of the figures are made, the designer tries to pour into the skin media, sculpted, and given coloring just like the process of making shadow puppets (purwa). The Wacinwa replica made includes puppets from Sie Jin Kwie and Khai Sou Bun. These puppets are the result of the interpretation of the designer based on the shape of the puppet collection of Sonobudoyo Museum and images in Sie Djin Koei Tjeng Tang’s comic works by Siaw Tik Kwie (Oto Suastika).Tujuan karya perancangan ini adalah membuat boneka Wacinwa yang disesuaikan dengan kepentingan dan kebutuhan si perancang dalam pertunjukan. Pembuatan wayang dilatarbelakangi oleh adanya kendala dalam hal ketersediaan wayang untuk pementasan. Sementara ini Wacinca hanya dimiliki oleh Museum Sonobudoyo Yogyakarta. Selain itu boneka Wacinwa koleksi Museum Sonobudoyo ukurannya terlalu kecil, kepalanya terlepas dari badan, dan sulit digerakkan. Tokoh-tokoh yangdibuat adalah tokoh dalam garap cerita Wacinwa berjudul Sang  Manggalayuda. Metode Hawkins (1991) tentang tahap-tahap merancang digunakan dalam karya ini. Adapun tahapan tersebut adalah pertama tahap eksplorasi, yaitu menetapkan tema, ide, dan judul karya serta berpikir, berimajinasi, merasakan, dan mencari dalam rangka menafsirkan ide dan gagasan. Tahap kedua adalah tahap eksperimentasi, yaitu mencoba untuk memilih, membedakan, mempertimbangkan dalam rangka mencari keharmonisan dan menemukan integritas serta kesatuan dalam berbagai percobaan. Tahap terakhir adalah tahap pembentukan, yaitu menentukan bentuk perancangan dengan menggabungkan simbol-simbol hasil dari uji coba yang dilakukan. Setelah gambar tokoh-tokoh tersebut jadi, perancang mencoba untuk menuangkan ke dalam media kulit, dipahat, dan diberi pewarnaan seperti halnya proses pembuatan wayang kulit (purwa). Replika Wacinwa yang dibuat antara lain wayang tokoh Sie Jin Kwie dan Khai Sou Bun. Wayang-wayang ini merupakan hasil interpretasi perancang berdasarkan bentuk wayang koleksi Museum Sonobudoyo dan gambar dalam komik Sie Djin Koei Tjeng Tang karya Siaw Tik Kwie (Oto Suastika).